Efektivitas Peran Bpbd Dalam Upaya Rehabilitasi Dan Rekonstruksi Rumah Masyarakat Pasca Bencana Banjir Di Nagari Tanjung Sani Kabupaten Agam - Rizana, Wahyu; Alhadi, Zikri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
This study intends to find out the effectiveness of the role of BPBD in the rehabilitation and reconstruction of community houses after the flood disaster that occured in Agam Regency, namely Jorong Galapung Nagari Tanjung Sani Tanjung Raya District. This research is motivated by the constraints found in the rehabilitation and reconstruction efforts of community houses carried out by BPBD Agam Regency, namely inaccurate data or information obtained in the field, lack of community participation in socialization related to rehabilitation and reconstruction, BPBD lacking in providing information regarding requirements and the timing of the rehabilitation and reconstruction, and lack of funds. In conducting this research, researcher used a qualitative approach using descriptive methods, then in determining the informants in this study the researcher used purposive sampling methods and techniques. Whereas in the data collection technique, researchers did it through interviews, observation and documentation. In testing the validity of the data, the researcher used the method triangulation technique. Meanwhile, in analyzing the data, the researcher used data reduction methods, data presentatin, and conclusions. The results of this study indicate that BPBD has been effective in carrying out the rehabilitation and reconstruction of community houses.